2018
DOI: 10.1002/da.22738
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neuroplasticity in the prefrontal cortex in depression indexed through paired associative stimulation

Abstract: Our findings provide evidence for impaired neuroplasticity in DLPFC in patients with depression compared to healthy subjects. Such findings may ultimately help us understand the pathophysiology of MDD and mechanisms involved in its treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 70 publications
(96 reference statements)
5
34
0
Order By: Relevance
“…From a more cognitive perspective, it would have been of interest to assess neural plasticity induced in the dorsolateral PFC (DLPFC), a brain region critically involved in the pathophysiology of MDD (Concerto et al, 2015). In line with this, combining EEG and TMS, Noda et al (2018) reported an impaired neuroplasticity in the DLPFC of patients with MDD compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 68%
“…From a more cognitive perspective, it would have been of interest to assess neural plasticity induced in the dorsolateral PFC (DLPFC), a brain region critically involved in the pathophysiology of MDD (Concerto et al, 2015). In line with this, combining EEG and TMS, Noda et al (2018) reported an impaired neuroplasticity in the DLPFC of patients with MDD compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 68%
“…Studies old [15,16,17] and new [18,19,20] find that depression affects many brain regions. Prominent brain regions with both functional and structural differences in depression are the frontolimbic brain regions such as the amygdala, hypothalamus, and prefrontal cortex (PFC) [21,22] (for review, see References [23,24]). Dysfunctional connectivity between these regions via an amygdala–striatal–pallidial–thalamic–cingulate cortex circuit is also found dysfunctional in depression [14,25].…”
Section: Neurobiology Of Depressionmentioning
confidence: 99%
“…Interestingly, dysfunction, by way of decreased perfusion in the PFC, has been reported in patients who attempted suicide. It is thought this PFC dysfunction might reduce problem-solving ability, increase negative emotions, and, finally, aid suicidal behaviour especially given the role of the orbitofrontal cortex in response inhibition [22,40].…”
Section: The Importance Of the Pfcmentioning
confidence: 99%
“…Depressed individuals show reduced PAS in the dorsolateral prefrontal cortex (DLPFC) compared with healthy individuals, suggesting reduced neuro plasticity. 38 Selective serotonin reuptake inhibitors (SSRIs) affect neuroplasticity induced by transcranial direct current stimulation (tDCS), as detected by repetitive TMS (rTMS)-evoked motor cortex responses or PAS responses. [39][40][41] Recently, magnetic seizure therapy has been shown to provoke changes in the excitability of the frontal cortex that correlate with a reduction in suicidal ideation.…”
Section: J Psychiatry Neurosci 2019;44(3)mentioning
confidence: 99%